2014
DOI: 10.24925/turjaf.v3i4.204-206.247
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Education and Farmers’ Wealth in Bangladesh

Abstract: The impact of farmers' education is examined with a view to evaluate the actual situation of farmers' education in Bangladesh. Fifty samples were collected from two sub districts of the Gazipur district in Bangladesh. The selection of the study sites and collection of the samples such as the years of schooling of the farm household head, total income, farm size, number of earners of farm families, family size, years of farming experience of farm household head, number of times extension contacts and rice yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The average annual income of the farmers in the study area was BDT 2, 30,770 ($2,884.63 US), which is more than the national average of household income BDT 1, 37,748 ($1721 US) (HIES, 2010). The similar findings found in the study conducted by Haq (2016 …”
Section: Descriptive Information Of the Farmerssupporting
confidence: 81%
“…The average annual income of the farmers in the study area was BDT 2, 30,770 ($2,884.63 US), which is more than the national average of household income BDT 1, 37,748 ($1721 US) (HIES, 2010). The similar findings found in the study conducted by Haq (2016 …”
Section: Descriptive Information Of the Farmerssupporting
confidence: 81%
“…From another perspective, the farmers' prosperity is not only related to income, but also material profits (Puspitasari, 2015). Early study by Mahmudul (2014) concluded that famer education is necessary to improve farmer wealth. His study has also found that farmers' wealth or prosperity is determined significantly by farmer size of family and years of farming experience.…”
Section: Results Discussionmentioning
confidence: 99%